2002
DOI: 10.1155/s1110865702000914
|View full text |Cite
|
Sign up to set email alerts
|

Chip-Level Channel Equalization in WCDMA Downlink

Abstract: The most important third generation (3G) cellular communications standard is based on wideband CDMA (WCDMA). Receivers based on TDMA style channel equalization at the chip level have been proposed for a WCDMA downlink employing long spreading sequences to ensure adequate performance even with a high number of active users. These receivers equalize the channel prior to despreading, thus restoring the orthogonality of users and resulting in multiple-access interference (MAI) suppression. In this paper, an overvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2007
2007
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(31 citation statements)
references
References 34 publications
0
31
0
Order By: Relevance
“…If the IPI is partially suppressed by an interference canceller [4] or an equalizer [5], the throughput increases. We have shown that a combined use of IPI canceller and random TPC provides a significant improvement in the throughput of DS-CDMA slotted ALOHA [6]. Recently, frequency-domain equalization (FDE) [7], [8] has been attracting much attention to improve the single-carrier transmission performance in a frequencyselective channel.…”
Section: Introductionmentioning
confidence: 99%
“…If the IPI is partially suppressed by an interference canceller [4] or an equalizer [5], the throughput increases. We have shown that a combined use of IPI canceller and random TPC provides a significant improvement in the throughput of DS-CDMA slotted ALOHA [6]. Recently, frequency-domain equalization (FDE) [7], [8] has been attracting much attention to improve the single-carrier transmission performance in a frequencyselective channel.…”
Section: Introductionmentioning
confidence: 99%
“…We also only need to compute d21 and d22 to get the G elements. The redundant computations in {tmp 4 , tmp 8 …”
Section: Parallel Architecture Modulesmentioning
confidence: 99%
“…With a very short spreading gain, the conventional Rake receiver could not provide acceptable performance. Linear-MinimumMean-Square-Error (LMMSE) chip equalizer is promising to restore the orthogonality of the spreading code, so as to suppress both the ISI and MAI [4]. However, it requires to inverse a large correlation matrix with O((N F )…”
Section: Introductionmentioning
confidence: 99%
“…With a very short spreading gain, the conventional Rake receiver could not provide acceptable performance. The LMMSE (LinearMinimum-Mean-Square-Error)-based chip equalizer is promising to restore the orthogonality of the spreading code, so as to suppress both the ISI and MAI [5].…”
Section: Introductionmentioning
confidence: 99%
“…The fact that the receiver must be embedded into a portable device makes the design of low complexity mobile receivers very critical for widespread commercial deployment of low cost products. To avoid the Direct-Matrix-Inverse (DMI), adaptive stochastic gradient algorithms such as LMS could be applied [5]. However, they suffer from stability problems because the convergence depends on the choice of good step size.…”
Section: Introductionmentioning
confidence: 99%